First Synthesis of Lissoclimide-Type Alkaloids (2009)
ABSTRACT: The first synthesis of lissoclimide-type alkaloids is described. Starting from commercial (+)-sclareolide, the al-dehyde-bicyclohomofarnesal is synthesized and coupled, through an aldol reaction, with succinimide. The antitumor activity of several lissoclimide analogues is also reported.